A szocializmus és a kommunizmus : . az emberiség igazi történelmének hajnala. . Socialism and communism : the true dawn of human history (Magyar Diafilmgyártó Vállalat, 1962)
Produced for the Central Committee of the Communist Youth Association, Department for Agitation and Propaganda.